2019
DOI: 10.3389/fnhum.2019.00056
|View full text |Cite
|
Sign up to set email alerts
|

EEG Microstates Temporal Dynamics Differentiate Individuals with Mood and Anxiety Disorders From Healthy Subjects

Abstract: Electroencephalography (EEG) measures the brain’s electrophysiological spatio-temporal activities with high temporal resolution. Multichannel and broadband analysis of EEG signals is referred to as EEG microstates (EEG-ms) and can characterize such dynamic neuronal activity. EEG-ms have gained much attention due to the increasing evidence of their association with mental activities and large-scale brain networks identified by functional magnetic resonance imaging (fMRI). Spatially independent EEG-ms are quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 64 publications
6
59
0
Order By: Relevance
“…The aim is to obtain a low value of CV. The active microstate prototypes obtained in this study are consistent with the normative EEG microstate classes identified by many studies 40,41,87,[109][110][111] . Following the selection of an active number of microstate prototypes, the EEG of each volunteer is re-expressed as a sequence of microstate classes by back-fitting these active microstate prototypes on each volunteer's EEG Figure 9.…”
Section: Assessment Of Frontal Hemispherical Asymmetry Measuressupporting
confidence: 88%
See 1 more Smart Citation
“…The aim is to obtain a low value of CV. The active microstate prototypes obtained in this study are consistent with the normative EEG microstate classes identified by many studies 40,41,87,[109][110][111] . Following the selection of an active number of microstate prototypes, the EEG of each volunteer is re-expressed as a sequence of microstate classes by back-fitting these active microstate prototypes on each volunteer's EEG Figure 9.…”
Section: Assessment Of Frontal Hemispherical Asymmetry Measuressupporting
confidence: 88%
“…However, the microstate analysis employed in the current study uses an average referencing scheme for frontal alpha asymmetry estimation. The present study follows average referencing for microstate analysis as various studies 40,87 adequately understand the cognitive phenomena through average-referenced microstate estimations. Further, the effect of different EEG referencing schemes on microstate estimations is still not clearly understood.…”
Section: Absence Of Correlation Among Proposed Microstate and Standarmentioning
confidence: 99%
“…To date, measures of the duration, rate of occurrence, and the sequence of specific microstate configurations have been associated with individual differences in age and gender (Koenig et al, 2002;Tomescu et al, 2018), as well as clinical and neurological diagnoses and dysfunction (Rieger et al, 2016;Zoubi et al, 2019). Information regarding the association of microstate parameters with personality attributes or with cognitive performance measures is even more limited.…”
mentioning
confidence: 99%
“…Microstates appear to be useful to identify novel diagnostic and treatment options for schizophrenia patients, 28 for the diagnosis of psychotic disorders 164 and bipolar disorder, 187 to reveal depressive symptomatology during depressive episodes 165 and to identify aberrant neural dynamics in patients affected by mood and anxiety disorders. 166 Resting state measures such as frontal alpha asymmetry, prefrontal theta cordance or EEG-vigilance regulation seem to have the potential to serve as predictive biomarkers to inform the choice of treatment, for example, in affective disorders. 38,39,188 In this view, the COVID-19 impact on psychiatric electrophysiological research was tremendously negative.…”
Section: Discussionmentioning
confidence: 99%
“…158,159 The results of these microstates and functional connectivity analyses may have an impact on clinical applications such as schizophrenia, 28,162,163 psychosis, 164 depression, 165 and mood and anxiety. 166 A more recent application of functional connectivity concerns the study of how information is exchanged between individuals during the performance of a common task (hyperbrain studies). The results from hyperbrain scanning have helped elucidate neural mechanisms of social interaction and have identified neural networks and electrophysiological biomarkers associated with cooperative and competitive behaviors (for reviews, see Czeszumski et al 167 and Balconi and Vanuelli 168 ).…”
Section: • • Microstates and Connectivity: A Body Of Research In Eegmentioning
confidence: 99%